Temple Management Communication Strategy in Relocating Traders in the Besakih Temple Area - Bagus Ade Tegar Prabawa; Made Ika Kusuma Dewi; Ni Nyoman Ayu Swarthini; Luh Komang Adinda Swadanasari; I Made Divpa Jaya Kusuma (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2023)
The Nangun Sat Kertih Loka Bali program encompasses the arrangement of the Besakih Temple area in the construction of parking facilities, kiosks, sanitation facilities, and other suitable amenities in the Besakih Temple area. The kiosks built in the arrangement of the Besakih Temple area aim to facilitate traders who sell within the temple grounds, thus enhancing the local economy and regulating unauthorized vendors in the Besakih Temple area. The current challenge faced by the government is relocating these vendors away from the temple area and asking them to move to designated locations. Naturally, this relocation process has met with strong protests from the vendors, necessitating effective communication strategies by the government to achieve the desired outcomes. The objectives of this research are to describe the communication strategies and the implementation of communication strategies employed by the Temple Management in the effort to relocate vendors in the Besakih Temple area. The method used in this research is qualitative descriptive. The results of this research include: 1) The government conducted research to identify the issues arising from the vendor relocation. 2) The government formulated a communication plan, which includes: (a) Sending messages or notifications to the vendors. (b) Selecting the appropriate communication channels. (c) Establishing an integrated team as communicators. (d) Collecting feedback from both parties. 3) During the relocation implementation phase, several issues were identified, including: (a) Resistance from some vendors. (b) Reduced visitors in the Bencingah Area. (c) Some vendors expressing satisfaction with the relocation. (d) Reduced traffic congestion during the Karya Betara Turun Kabeh ceremony. (e) Besides constructing vendor kiosks, free transportation, selfie spots, parking areas, public toilets, and meeting halls were provided. 4) The evaluation phase includes: (a) Resistance from vendors to relocation. (b) The community parking area has not been fully utilized